A narrative review on the use of probiotics in several diseases. Evidence and perspectives - Campaniello, Daniela; Bevilacqua, Antonio; Speranza, Barbara; Racioppo, Angela; Sinigaglia, Milena; Corbo, Maria Rosaria (Frontiers in Nutrition, 2023)
Gut microbiota is a complex ecosystem, strictly linked to health and disease, as a balanced composition (referred as eubiosis) is necessary for several physiological functions, while an unbalanced composition (dysbiosis) is often associated to pathological conditions and/or diseases. An altered microbiota could be positively affected and partially restored through probiotic supplementation, among others. This review addresses the effects of probiotics in several conditions, used as case-studies (colorectal cancer, neuro-psychiatric diseases, intestinal diseases, obesity, diabetes, metabolic syndrome, immune system, and musculoskeletal system disorders) by pointing out the clinical outcomes, the mode of action, mainly related to the production of short chain fatty acids (SCFA), the impact of probiotic dose and mode of supplementation, as well as trying to highlight a hit of the most used genera.